Sodium Taurocholate Cotransporting Polypeptide (NTCP) Deficiency Hidden Behind Citrin Deficiency in Early Infancy: A Report of Three Cases - Lin, Hui; Qiu, Jian-Wu; Rauf, Yaqub-Muhammad; Lin, Gui-Zhi; Liu, Rui; Deng, Li-Jing; Deng, Mei; Song, Yuan-Zong (Frontiers in Genetics, 2019)
Sodium Taurocholate Cotransporting Polypeptide (NTCP), a carrier protein encoded by the gene SLC10A1, was expressed in the basolateral membrane of the hepatocyte to uptake bile acids from plasma. As a new inborn error of bile acid metabolism, NTCP deficiency remains far from being well understood in terms of the clinical and molecular features. Citrin deficiency is a well-known autosomal recessive disease arising from SLC25A13 mutations, and in neonates or infants, this condition presents as transient intrahepatic cholestasis which usually resolves before one year of age. All the 3 patients in this paper exhibited cholestatic jaundice and elevated total bile acids (TBA) in their early infancy, which were attributed to citrin deficiency by SLC25A13 genetic analysis. In response to feeding with lactose-free and medium-chain triglycerides-enrich formula, their clinical and laboratory presentations disappeared gradually while the hypercholanemia persisted, even beyond 1 year of age. On subsequent SLC10A1 analysis, they were all homozygous for the well-known pathogenic variant c.800C>T (p.Ser267Phe), and NTCP deficiency was thus definitely diagnosed. The findings in this paper indicated that NTCP deficiency could be covered up by citrin deficiency during early infancy; however, in citrin-deficient patients with intractable hypercholanemia following resolved cholestatic jaundice, NTCP deficiency should be taken into consideration.